Manajemen Penyuluhan Vaksinasi Oleh Bidang Kesehatan Puskesmas Waru Pamekasan - Jannah, S. Fathiyatul; Mukarromah, Kamilatul (STAI Publisistik Thawalib Jakarta, 2022)
Vaccination counseling aims to change the negative attitude of people who do not want to be vaccinated to a positive attitude that is willing to be vaccinated. The research method is a qualitative approach with the type of case study. Data collection techniques by observation, interviews and documentation. Techniques of data analysis with reduction, data presentation, and drawing conclusions. Technique of data validity with triangulation technique. The results showed that the management functions included: 1) Vaccination planning: materials, time, targets, location/place, methods, media, and budget. 2) Organizing vaccinations: head of vaccination counseling, secretary, treasurer, and vaccination instructor (health sector/doctor). 3) Implementation of offline seminars and public methods by placing posters and banners. 4) Controlling, first is the pre-extension control, namely the assessment of the feasibility of the readiness of the material, method, location, target, time, media, and cost.